2,4-Dibromo-6-{(E)-[(R)-1-phenylethyl]iminomethyl}phenol - Xia, Dong-Guo (International Union of Crystallography, 2009)
In the title Schiff base, C(15)H(13)Br(2)NO, the benzene and phenyl rings form a dihedral angle of 75.18 (13)°. The N=C bond length of 1.263 (6) Å is shorter than of the N—C bond [1.476 (5) Å], indicating a double bond. In the crystal, there is some pseudosymmetry. This occurs because most of the two molecules are centrosymmetrically related. The molecular structure is stabilized by intramolecular O—H⋯N hydrogen bonds.